Integration of Active Solar Thermal Technologies in Greenhouses: A Mini Review - Ding, Ding (Frontiers in Energy Research, 2021)
Traditional agricultural greenhouses have been used to grow vegetables in the winter without any auxiliary heating. However, crop production is highly influenced by soil and air temperatures, humidity, and solar radiation. The aim of this paper is to review the recent active solar thermal technologies that help reduce the energy demand for greenhouse climate control and achieve intensive crop production. The review is categorized into the following topics: (1) locations for collector installation; (2) discussion on the different types of solar collectors, which include metal-based, glass-based, ceramic-based, plastic-based, and hybrid photovoltaic/thermal types for greenhouse applications; (3) heat release systems in active greenhouses in terms of basal heating, backwall heating, and air heating systems; and (4) short-term and long-term heat storage systems for greenhouses. Future studies on active solar greenhouses might focus on microclimate prediction, long-term heat storage, and system optimization.